Children With Speech Delay And Disorders : Ooi Shi Jing A Case Study On The Clinical Practices And Interventions Used By The Professionals, And The Challenges They Faced - Ooi, Shi Jing (Universiti Malaysia Sarawak, (UNIMAS), 2017)
The number of children with speech difficulties in Malaysia has risen over the years and it is very important for professionals to carry out early intervention in order to control such phenomena. Current study aimed to investigate the practices and interventions used by speech-language therapists and pathologists (SLTPs) on children with speech delay and disorders. Furthermore, this study also investigated the treatment procedures used by SL TPs, as well as addressed the challenges they faced while providing treatment. Interview was done with 15 SLTPs from two urban settings and observation was done for setting description. Results indicated that the commonly used approaches were goal-based approach, parental coaching, gestures, talk tools for children with om-motor issues, play-based approach and minimal pairs specifically for child with phonological difficulties. Formal initial assessment was used and reassessment was done in periodical or on-going form. Observation showed that the setting of therapy room was divided into three categories which include playroom setting, office setting and combination of both. Generally, most SLTPs used combination of both traditional and functional approach which carrying out the treatment. Common challenges that SL TPs faced were parent issues and incomplete sessions.